Changes in local and spatial identity in the process of peri-urbanization in Tacna - Carpio Zapata , Maria Flavia (2024)
The accelerated and disorganized growth of cities in Latin America has generated a key phenomenon: periurbanization, a process in which the boundaries between urban and rural areas become blurred, transforming the physical landscape and local identity. In Tacna, Sector 14: Campiña Sur, historically agricultural, faces uncontrolled urban expansion driven by real estate speculation and lack of planning. This article analyzes the changes in the local and spatial identity of this area, revealing how social, economic, and cultural dynamics intertwine with increasing urbanization. Through qualitative research, which includes field observation and interviews, the loss of agricultural land is evidenced, displacing traditions and ways of life due to the disconnection between local authorities, private actors, and the community. The findings suggest the urgency of adopting sustainable, comprehensive, and participatory urban planning approaches, where the preservation of territory, local identity, and equitable access to services are priorities.